Adjuvant Therapy Effect of Curcuma Longa Rhizome Extract On TGF-β Serum Levels in Leprosy Ulcer Patients - Alfarizi, Rizki; Yuniati, Renni; Mundhofir, Farmaditya Eka Putra; Wijayahadi, Noor; Nindita, Yora (Syntax Corporation Indonesia, 2024)
Leprosy ulcer is one of the worsening manifestations of leprosy that often causes disability if not appropriately handled. Healing of ulcers requires a long enough duration so that a good immunological response is needed to encourage the wound healing process, one of which is transforming growth factor- (TGF-), which is necessary of the plants that plays a role in the expression of TGF- to spur wound healing is Curcuma longa rhizome or turmeric rhizome. This study is expected to prove that administering Curcuma longa rhizome extract can increase serum TGF-β levels in leprosy ulcer patients. This study is an experimental study with a pre and post-randomised single-blind controlled trial design involving 22 subjects with leprosy ulcers. The control group obtained standard therapy for leprosy ulcers, and the treatment group received standard therapy and adjuvant Curcuma longa rhizome extract at a dose of 1 g per day for 30 days. TGF-β levels were measured by the ELISA method. Data analysis used the Wilcoxon test and the Mann-Whitney test. The results showed no significant difference in TGF-β levels after and before the intervention in the control group (p=0.79) and the treatment group (p=0.14). However, there was a significant difference in TGF-β levels after the intervention in the control group and treatment (p=0.01). Curcuma longa rhizome extract did not show an important role in changes in serum TGF-β levels in leprosy ulcer patients. This study showed that administering Curcuma longa rhizome extract for 1 month did not show a potential role as an adjuvant therapy. Leprosy ulcer is one of the worsening manifestations of leprosy that often causes disability if not appropriately handled. Healing of ulcers requires a long enough duration so that a good immunological response is needed to encourage the wound healing process, one of which is transforming growth factor- (TGF-), which is necessary of the plants that plays a role in the expression of TGF- to spur wound healing is Curcuma longa rhizome or turmeric rhizome. This study is expected to prove that administering Curcuma longa rhizome extract can increase serum TGF-β levels in leprosy ulcer patients. This study is an experimental study with a pre and post-randomised single-blind controlled trial design involving 22 subjects with leprosy ulcers. The control group obtained standard therapy for leprosy ulcers, and the treatment group received standard therapy and adjuvant Curcuma longa rhizome extract at a dose of 1 g per day for 30 days. TGF-β levels were measured by the ELISA method. Data analysis used the Wilcoxon test and the Mann-Whitney test. The results showed no significant difference in TGF-β levels after and before the intervention in the control group (p=0.79) and the treatment group (p=0.14). However, there was a significant difference in TGF-β levels after the intervention in the control group and treatment (p=0.01). Curcuma longa rhizome extract did not show an important role in changes in serum TGF-β levels in leprosy ulcer patients. This study showed that administering Curcuma longa rhizome extract for 1 month did not show a potential role as an adjuvant therapy.